2003
DOI: 10.1046/j.1468-1293.2003.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose indinavir in combination with low‐dose ritonavir: steady‐state pharmacokinetics and long‐term clinical outcome follow‐up

Abstract: Treatment with the IDV/RTV 400/100 mg regimen appears to be efficacious for up to 2 years. However, rather low IDV Cmin suggests that the regimen should be evaluated further before its widespread use and that the regimen probably should be guided by pharmacokinetic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In another small retrospective trial, Justesen et al . found that 70% of 21 patients (either ART‐naive or IDV 800 mg tid experienced subjects) treated with IDV/RTV 400/100 mg bid achieved a viral load <20 copies/mL after a median of 116 weeks [16]. Both studies found low rates of adverse events, but no comparison was made with other dosages of IDV.…”
Section: Discussionmentioning
confidence: 99%
“…In another small retrospective trial, Justesen et al . found that 70% of 21 patients (either ART‐naive or IDV 800 mg tid experienced subjects) treated with IDV/RTV 400/100 mg bid achieved a viral load <20 copies/mL after a median of 116 weeks [16]. Both studies found low rates of adverse events, but no comparison was made with other dosages of IDV.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Apart from this, various other studies also support clinical usefulness of low-dose IDV/r-based treatment. 8,14,15,17,18 PK data also suggest that low-dose IDV/rbased treatment may not be adequate for patients weighing >55 kg. 14 Results of our study confirms that PI/r-based treatment is a good choice for second line in treatment of first-line NNRTIbased treatment failure with 14.8% of overall treatment failure with second-line regimen during the follow-up period.…”
Section: Visits (In Months)mentioning
confidence: 99%
“…12,13 Recent studies suggested that lowering of IDV/r dosage to 400/100 mg BID has retained same potency and has improved pharmacokinetic profiles. 8,[14][15][16][17][18] Atazanavir boosted with ritonovir (ATV/r) is an advantageous PI due to its oncedaily dosage and reduced effect on patient's lipid profile. 19,20 Some study findings suggest that these drugs have the same efficacy as LPV/r.…”
Section: Introductionmentioning
confidence: 99%
“…The difference was observed consistently on all three study days, and the same result was found in subjects admitted the previous day, when we timed their evening dose. This difference most likely reflects diurnal variation in indinavir concentrations, a phenomenon that has been previously noted for indinavir as well as for other protease inhibitors (PIs) (7,8). In light of this difference, it would be advisable for all future research studies of PIs to include measurements of both morning and evening C min s.…”
mentioning
confidence: 95%
“…A small group of patients with undetectable virus loads switching from unboosted indinavir to 400 mg of indinavir with ritonavir given twice daily maintained viral suppression at 48 weeks (5). In contrast, in patients with detectable viral loads and previous PI exposure, switching to 400 mg of indinavir resulted in some treatment failures (7). Therefore, the 400-mg dose of indinavir may best be avoided for patients who have previously experienced PI failure, in whom the 95% inhibitory concentration may be raised above that for a wild-type virus (4).…”
mentioning
confidence: 99%